Pengaruh Penggunaan Media Interaktif Terhadap Motivasi Belajar Peserta Didik Kelas II Mata Pelajaran Pendidikan Pancasila Di SD Negeri 2 Tanjung Benoa Kabupaten Badung - Ni Kadek Jeni Krisnawati; Ni Gusti Ayu Made Yeni Lestari; Ni Nyoman Suastini (Jurnal Pustaka Cendekia Pendidikan, 2026)
AbstractPancasila Education plays an important role in developing students’ character and moral values. However, thelearning motivation of second-grade students at SD Negeri 2 Tanjung Benoa remains relatively low due to thelimited and less varied use of learning media. This study aimed to determine the effect of interactive media onstudents’ learning motivation and to analyze the differences in learning motivation between students who usedinteractive media and those who learned through conventional methods. This research employed a quantitativeapproach with an experimental design involving an experimental class and a control class. Data were collectedthrough questionnaires, observations, interviews, and documentation. The data were analyzed using descriptivestatistics and inferential statistics through the Independent Sample t-test. The results showed that the use ofinteractive media had a significant effect on students’ learning motivation in Pancasila Education. TheIndependent Sample t-test produced a significance value of 0.012 < 0.05, indicating that H₀ was rejected and Hₐwas accepted. Students in the experimental class demonstrated higher learning motivation than those in thecontrol class. These findings indicate that interactive media can serve as an effective learning alternative toimprove students’ learning motivation in Pancasila Education.Keywords: Interactive Media, Learning Motivation, Pancasila Education, Elementary School, Learning.